Amantadine modulates novel macrophage phenotypes to enhance neural repair following spinal cord injury - Shijie Yang; Beibei Yu; Qing Zhang; Yongfeng Zhang; Longhui Fu; Bisheng Zhou; Haining Wu; Jianzhong Li; Shouping Gong (Journal of Translational Medicine)
Abstract Background Spinal cord injury (SCI) triggers a complex inflammatory response that impedes neural repair and functional recovery. The modulation of macrophage phenotypes is thus considered a promising therapeutic strategy to mitigate inflammation and promote regeneration. Methods We employed microarray and single-cell RNA sequencing (scRNA-seq) to investigate gene expression changes and immune cell dynamics in mice following crush injury at 3 and 7 days post-injury (dpi). High-dimensional gene co-expression network analysis (hdWGCNA) and slingshot trajectory analysis were employed to identify key gene modules and macrophage differentiation pathways. Subsequently, immunofluorescence staining, flow cytometry, and western blotting were performed to validate the identified effects of amantadine on macrophage differentiation and inflammation. Results To elucidate the molecular mechanisms underlying the injury response at the transcriptional level, we performed a microarray analysis followed by gene set enrichment analysis (GSEA). The results revealed that pathways related to phagocytosis and macrophage activation are significantly involved post-injury, shedding light on the regulatory role of macrophages in SCI repair. To further investigate macrophage dynamics within the injured spinal cord, we conducted scRNA-Seq, identifying three distinct macrophage subtypes: border-associated macrophages (BAMs), inflammatory macrophages (IMs), and chemotaxis-inducing macrophages (CIMs). Trajectory analysis suggested a differentiation pathway from Il-1b+ IMs to Mrc1+ BAMs, and subsequently to Arg1+ CIMs, indicating a potential maturation process. Given the importance of these pathways in the injury response, we utilized molecular docking to hypothesize that amantadine might modulate this process. Subsequent in vitro and in vivo experiments demonstrated that amantadine reduces Il-1b+ IMs and facilitates the transition to Mrc1+ BAMs and Arg1+ CIMs, likely through modulation of the HIF-1α and NF-κB pathways. This modulation promotes neural regeneration and enhances functional recovery following SCI. Conclusions Amantadine modulates macrophage phenotypes following SCI, reduces early inflammatory responses, and enhances neural function recovery. These findings highlight the therapeutic potential of amantadine as a treatment for SCI, and provide a foundation for future translational research into its clinical applications.